Gut microbial diversity in Apis cerana indica and Apis florea colonies: a comparative study - Khan, Khalid Ali; Ganeshprasad, D. N.; Sachin, H. R.; Shouche, Yogesh S.; Ghramh, Hamed A.; Sneharani, A. H. (Frontiers in Veterinary Science, 2023)
Introduction Honey bee gut microbiota have an important role in host health, nutrition, host-symbiont interaction, and interaction behavior with the surrounding environment. Recent discoveries of strain-level variation, characteristics of protective and nutritional capabilities, and reports of eco-physiological significance to the microbial community have emphasized the importance of honey bee gut microbiota. Many regions of Asia and Africa are inhabited by the dwarf honey bee, Apis florea. Studying its microflora and potential for pollination is therefore of foremost importance. Methods In the present investigation, we aimed to explore the gut bacteriobiome composition of two distinct honey bee species, Apis florea and Apis cerana indica using high throughput sequencing. Functional predictions of bee gut bacterial communities using PICRUSt2 was carried out. Results and discussion The phylum Proteobacteria dominated the bacterial community in both A. cerana indica (50.1%) and A. florea (86.7%), followed by Firmicutes (26.29 and 12.81%), Bacteroidetes (23.19 and 0.04%) and Actinobacteria (0.4 and 0.02%) respectively. The gut bacteria of A. cerana indica was more diverse than that of A. florea. The observed variations in bacterial genomic diversity among these critical pollinator species may have been influenced by the apiary management techniques, ecological adaptation factors or habitat size. These variations can have a significant effect in understanding host-symbiont interactions and functioning of gut microbiota highlighting the importance of metagenomic survey in understanding microbial community ecology and evolution. This is the first comparative study on variation in bacterial diversity between two Asian honey bees.